Targeting microRNAs in diabetic retinopathy: from pathogenic mechanisms to therapeutic potentials - Chen, Jiajun; Zhang, Jingjing; Li, Changlei; Wang, Ling; Tao, Long; Xue, Shasha; Wang, Fenglei (Frontiers in Endocrinology, 2025)
Diabetic retinopathy (DR), a prevalent microvascular complication affecting diabetic patients, imposes a significant global burden. Current therapies like anti-vascular endothelial growth factor (anti-VEGF) agents, offering limited efficacy in early stages and posing challenges related to invasiveness and recurrence. This underscores the urgent need for novel strategies targeting early intervention. This review proposes a unifying hypothesis: microRNAs (miRNAs) function as master regulators that integrate and amplify hyperglycemia-induced damage across multiple pathological axes—oxidative stress, inflammation, neurodegeneration, and vascular dysfunction. Dysregulation of specific miRNAs not only contribute to DR pathogenesis through multi-target modulation of key pathways but also exhibit stage-specific expression patterns in biofluids, positioning them as promising non-invasive biomarkers. Furthermore, miRNA-based therapeutic interventions, leveraging tools like quantitative reverse transcriptase PCR (qRT-PCR), droplet-based digital PCR (ddPCR), and microarrays for profiling, hold revolutionary potential to modulate key pathological cascades, and ultimately enable precision management strategies for early intervention and prevention of DR progression.